(untitled) (Global Scientific Review, 2023)
Study This mean For know influence method multisensory to ability read start students in class I SDN No. 48 Hulontalangi City of Gorontalo. Method study This use approach quantitative with form pre-experimental designs with type one group pretest-posttest design . Variable in study This is variable independent (X) ie method multisensory whereas variable dependent (Y) ie ability read start. Population study is student class One taken in a manner saturated sampling a total of 17 students . Data collection techniques include test read beginning ( pretest and posttest ) whereas observation and documentation as complement . Data analysis technique used is the data normality test and hypothesis testing. Earnings pretest average value of 42.65 and the average value of the posttest of 56.59. Research results strengthened with t test results using level significant 0.05 which mentions that t count > t table ie 21.12 > 2.11. So that H 0 rejected and Ha accepted. concluded that results study This show there is influence method multisensory to ability read start students in class I SDN No. 48 Hulontalangi City of Gorontalo.